Myths to debunk: the non-compacted myocardium. (18th November 2020) - Di Toro, Alessandro; Giuliani, Lorenzo; Smirnova, Alexandra; Favalli, Valentina; Serio, Alessandra; Urtis, Mario; Grasso, Maurizia; Arbustini, Eloisa
Abstract: Left ventricular non-compaction (LVNC) is defined by the triad: prominent trabecular anatomy, thin compacted layer, and deep inter-trabecular recesses. No person, sick or healthy, demonstrates identical anatomy of the trabeculae; their configuration represents a sort of individual dynamic 'cardiac fingerprinting'. LVNC can be observed in healthy subjects with normal left ventricular (LV) size and function, in athletes, in pregnant women, as well as in patients with haematological disorders, neuromuscular diseases, and chronic renal failure; it can be acquired and potentially reversible. When LVNC is observed in patients with dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy, restrictive cardiomyopathy, or arrhythmogenic cardiomyopathy, the risk exists of misnaming the cardiomyopathy as 'LVNC cardiomyopathy' rather than properly describe, i.e. a 'DCM associated with LVNC'. In rare infantile CMPs (the paradigm is tafazzinopathy or Barth syndrome), the non-compaction (NC) is intrinsically part of the cardiac phenotype. The LVNC is also common in congenital heart disease (CHD) as well as in chromosomal disorders with systemic manifestations. The high prevalence of LVNC in healthy athletes, its possible reversibility or regression, and the increasing detection in healthy subjects suggest a cautious use of the term 'LVNC cardiomyopathy', which describes the morphology, but not the functional profile of the cardiac disease. Genetic testing, when positive, usually reflects the genetic causes of an underlying cardiomyopathy rather than that of the NC, which often does not segregate with CMP phenotype in families. Therefore, when associated with LV dilation and dysfunction, hypertrophy, or CHD, the leading diagnosis is cardiomyopathy or CHD followed by the descriptor LVNC.